E-Learning Model to Support Industrial Based Adaptive Learning for Student Vocational High School - Rian Andrian; Ahmad Fauzi (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
Vocational High Schools have an important role in improving the quality of human resources to meet industrial needs. However, the current education system in Vocational Schools especially in Purwakarta, Subang, Karawang, Bekasi (PURWASUKASI) still has disadvantages compared to other countries. The government through the ministry of industry has started vocational education for Vocational Schools in Indonesia. Vocational education conducted to support the creation of qualified human resources that can meet the industrial needs related to labor. The implementation of information technology in the field of education is one of the ways to improve the quality of education, including education in vocational schools. E-learning implementation aims to improve the quality of education. E-learning is often used in the application of adaptive learning in the field of education. In this study, an e-learning system model has been created that has been developed to support industrial based adaptive learning for Vocational High Schools in PURWASUKASI. The system that has been developed has been tested from the functional side of the system and shows that the developed e-learning system is ready to use.